Calcium sources compared in liquid feed supplements for finishing steers - Harbers, L.H.; Teague, R.D.; Riley, Jack G. (Kansas State University. Agricultural Experiment Station, 2011)
When calcium chloride was added to a mixture of minerals and urea in molasses, the minerals had not settled after the mixture was shipped 350 miles and stored 4 weeks. Calcium carbonate added to a similar supplement caused all minerals tested except sodium, potassium, and copper to precipitate. Using a 112-day, steer-feeding trial, we found that animals performed similarly when their liquid feed supplement contained either calcium chloride or resuspended calcium carbonate.
Keywords: Beef; Calcium carbonate; Finishing steers; Calcium chloride